Overview of the ant genus Vollenhovia (Hymenoptera, Formicidae) in India and Sri Lanka, with an illustrated key and the description of a new species - Shahid Ali Akbar; Himender Bharti; Enrico Schifani; Aijaz Ahmad Wachkoo (European Journal of Taxonomy, 2023)
The ant genus Vollenhovia Mayr, 1865 (Myrmicinae, Crematogastrini) mostly occurs in the Australasian and Oriental regions. We revised its diversity in India and Sri Lanka based on qualitative and quantitative morphology, recognizing eleven taxa, including a new species which is described herewith: V. escherichi Forel, 1911, V. gastropunctata Bharti & Kumar, 2013, V. karimalaensis Dhadwal et al., 2023, V. keralensis Kripakaran & Sadasivan, 2022, V. mawrapensis Dhadwal et al., 2023, V. oblonga laevithorax Emery, 1889, V. penetrans (Smith, 1857), V. pfeifferi Bharti et al., 2023, V. taylori Rilta et al., 2023, V. terayamai Rilta et al., 2023, and V. yasmeenae sp. nov. The subspecies status of V. oblonga laevithorax and its relationship with V. penetrans, whose type series does not contain workers, still requires to be assessed in the context of a broader revision including the whole Oriental region. The known distribution of the genus in the Indian subcontinent appears to be fragmentary, still requiring extensive sampling efforts. Four species are from the Western Ghats biodiversity hotspot in the southern Indian state of Kerala, one is endemic to the biogeographically related Sri Lanka, three are known from Eastern India near the border with Bangladesh, two are reported from the Andaman and Nicobar Islands, and one is restricted to the Himachal Pradesh in northern India. A comprehensive key of the known Vollenhovia species from India and Sri Lanka is provided.